Instructional Media Usage And Students’ Academic Performance In Colleges Of Education, Ghana - Nyagorme, Paul; Enoch, Sackey Ben; Arkorful, Valentina (Advances in Social Sciences Research Journal, 2017)
This study reported on the extent to which Instructional Media (IM) are being utilized at the Colleges of Education in Ghana and how IM utilization affect students’ academic performance. Quasi-experimental design was adopted for the study. Stratified sampling technique was used in selecting five Colleges from the thirty-eight (38) public Colleges of Education in Ghana. The actual sample size used for the study was Sixty-Seven (67) tutors from five selected Colleges of Education namely: Wiawso College of Education, St. Louis College of Education, Jasikan College of Education, Presbyterian Women’s College of Education and Bagabaga. The instruments used for data collection were questionnaire and interview. The collected data were analyzed using Statistical Package for Social Sciences (SPSS). From the analysis, it was revealed that instructional media were not adequately available in Colleges of Education in Ghana. Many Tutors were not competent enough in integrating technology into teaching and learning. From the analysis, students performed better in subjects where technology was used. It was therefore recommended that instructional media should be made available and accessible in the Colleges of Education; tutors should receive frequent technological training; tutors must be motivated to develop positive attitudes towards technology integration in Education. Again, teacher-trainees must be trained in the use of the various tools for educational purposes.